Energy performance and CO2 emissions of HVAC systems in commercial buildings - Al-Waked, R. (MDPI AG, 2017)
Energy performance of buildings has attracted much attention among building physicists and engineers worldwide. The effects of building heating; ventilation; and air conditioning (HVAC) systems' design upgrade on the building energy performance are the focus of the current study. The adopted HVAC system consisted of chilled ceiling and chilled beam systems served by a centrifugal water chiller. An energy simulation study was undertaken in accordance with the national Australian built environment rating system-rules for collecting and using data. A three-dimensional simulation study was carried out utilizing the virtual environment-integrated environmental solutions software. Results from the current study have shown the importance of utilizing energy-efficient HVAC systems and HVAC strategies for achieving a high building energy star rating. Recommended strategies in order to achieve the nominated star rating; as predicted by the simulation analysis; were presented. Moreover; the effects of solar radiation inside the building atrium were significant; which cannot be overcome by simply installing a low shading coefficient glazing type at the atrium skylight. In addition to providing chilled ceiling technology; a high efficiency chiller and low energy lighting; it is recommended that the building be well tuned during the commissioning period. The current approach could be extended to accommodate higher energy ratings of commercial buildings at different locations worldwide. © 2017 by the authors.